Wendy Richard - No 'S' : My Life Story - Richard, Wendy (London Simon & Schuster, 2000)
This is the life story of Wendy Richard, star of many classic television series. Her career has spanned over 30 years, appearing in shows such as Dad's Army, Are You Being Served? and Eastenders, she has also had a number one hit with Mike Sarne's Come Outside, and she has appeared on a variety of stage and screen productions. A recognizable personality, she tells of her life from her early days in Tee side, her influences and the personal and professional successes and traumas that have shaped her life.
Include Illustrations and Index.
Wendy Richard's My Life Story.
Keywords: Television actors and actresses -- Great Britain -- Richard, Wendy